Electrodeless sulfur lamp on the basis of microwave excitation: estimation of spectral effectiveness of radiation for bio-objects - Frolova, T. I. (Applied Radio Electronics: Sci. Journ, 2018)
The paper considers a lighting system based on an electrodeless sulfur lamp with microwave excitation for bioobjects. As a result of the intensive development of new technologies in the field of lighting equipment (LED, HID lamps, and others) it is necessary to replace outdated lighting for a more energy-efficient one, by using new modern lamps of artificial radiation for biological objects (human, animals and plants). The parameters of optical radiation sources for different biological objects are different (for humans and some animals they are based on the sensitivity of the eye (photonic response curve), for plants – it is the photon flux density of photosynthetically active radiation (PAR) from 400 to 700 nm). High-pressure sodium lamps (HPSL) and metal halide lamps (MHL) are the most common among the artificial light sources used in greenhouses. However, at present, the most effective and promising are lighting systems based on LED lamps and the electrodeless sulfur lamp with microwave excitation. The latter is environmentally friendly (it does not contain mercury), with a high efficiency of PAR (72%) and durable (above 60,000 hrs.) Analysis of the spectral efficiency of radiation showed that the electrodeless sulfur lamp with microwave excitation has a high photosynthetic photon flux density (PPFD) (1440 μmol·s-1·m-2) in an optical range of 400-700 nm.
Keywords: electrodeless sulfur lamp with microwave excitation; bio-object; sunlight; spectral irradiance; photosynthetically active radiation; photosynthetic photon flux density